Pendampingan Manajemen Konflik dalam Peningkatan Kinerja Guru di MAN 1 Langkat - Ahmad Zaki; Dian Anggeraini; Hafizh Hafizh (BADAN PENERBIT STIEPARI PRESS, 2022)
This mentoring activity aims to see the effectiveness of conflict management mentoring in improving teacher performance in educational environments. The problem identified is the existence of interpersonal conflict among teachers that has a negative impact on the work atmosphere and academic performance. The main objective of this study is to identify effective mentoring strategies in resolving conflicts and to evaluate their impact on improving teacher performance. The method used in this study is a qualitative approach with a case study design, involving in-depth interviews, observations, and document analysis to understand the dynamics of conflict and the effectiveness of the intervention. The results of the study indicate that the conflict management mentoring implemented can reduce interpersonal tensions, improve communication and cooperation among teachers, and significantly improve teacher performance and job satisfaction. These findings support the importance of implementing structured and evidence-based conflict management strategies in improving educational outcomes and a more harmonious work environment.